Optimizing the perception of soft speech and speech in noise with the Advanced Bionics cochlear implant system. - Holden, Laura K.; Reeder, Ruth M.; Firszt, Jill B.; Finley, Charles C. (International Journal of Audiology, 2011)
Abstract Objective: This study aimed to provide guidelines to optimize perception of soft speech and speech in noise for Advanced Bionics cochlear implant (CI) users. Design: Three programs differing in T-levels were created for ten subjects. Using the T-level setting that provided the lowest FM-tone, sound-field threshold levels for each subject, three additional programs were created with input dynamic range (IDR) settings of 50, 65 and 80 dB. Study sample: Subjects were postlinguistically deaf adults implanted with either the Clarion CII or 90K CI devices. Results: Sound-field threshold levels were lowest with T-levels set higher than 10% of M-levels and with the two widest IDRs. Group data revealed significantly higher scores for CNC words presented at a soft level with an IDR of 80 dB and 65 dB compared to 50 dB. Although no significant group differences were seen between the three IDRs for sentences in noise, significant individual differences were present. Conclusions: Setting Ts higher than the manufacturer's recommendation of 10% of M-levels and providing IDR options can improve overall speech perception; however, for some users, higher Ts and wider IDRs may not be appropriate. Based on the results of the study, clinical programming recommendations are provided. Sumario Objetivo: Este estudio buscóó proporcionar pautas para optimizar la percepcióón del lenguaje suave y del lenguaje en ruido para usuarios del implante coclear (IC) de Advanced Bionics. Diseñño: Se crearon tres programas para diez pacientes, que eran diferentes en sus niveles T. Al usar el control de nivel T que proporcionaba el tono FM máás bajo, con niveles de umbral en campo libre para cada sujeto, se crearon tres programas adicionales con controles de ingreso del rango dináámico IRD de 50, 65 y 80 dB. Muestra de Estudio: Los sujetos fueron sordos adultos postlingüüíísticos implantados con los modelos Clarion CII o 90K CI. Resultados: Los niveles de umbral en campo libre fueron máás bajos con los niveles T colocados 10% máás alto que los niveles M y con los dos IDR máás anchos. Los datos del grupo revelaron puntuaciones significativamente mayores con palabras CNC presentadas en un nivel suave con un IDR de 80 dB y 65 dB comparados con 50 dB. No obstante que no se encontraron diferencias significativas en los grupos entre los tres IDR para oraciones en ruido, si se presentaron diferencias significativas individuales. Conclusiones: La colocacióón de los niveles T máás altos en 10% que la recomendacióón del fabricante, sobre los niveles M y el proporcionar opciones de IDR, en general pueden mejorar la percepcióón del lenguaje; no obstante, niveles mayores de T y IDR máás anchas, pueden no ser apropiados para algunos usuarios. Con base en los resultados de este estudio, se proporcionan recomendaciones clíínicas para la programacióón.